Thymus persicus (Ronniger ex Rech. f.) Jalas alleviates nociceptive and neuropathic pain behavior in mice: Multiple mechanisms of action - Abed, Donya Ziafatdoost; Sadeghian, Reihaneh; Mohammadi, Saeed; Akram, Muhammad (Journal of ethnopharmacology, 2022)
Thymus persicus (Roniger ex Reach F.) is an Iranian endemic medicinal plant of which essential oil and various products have numerous food and pharmaceutical applications (headache and fever treatments). This modern research included Swiss mice to investigate the anti-nociceptive and anti-neuropathic effects of Thymus persicus aerial parts essential oil (TPEO). To determine TPEO's anti-nociceptive function in the formalin-induced paw licking (FML), researchers looked at the L-arginine/NO/cGMP/KATP channel signaling pathway as well as multiple receptors as with serotonin, morphine, dopamine, and peroxisome proliferator-activated receptors. The CVC or cervical spinal cord contusion exemplar has also been used to induce neuropathic pain. TPEO (50, 100, and 150 mg/kg) relative to control mice in the phase-II of FML provided strong antinociception (p < 0.05, p < 0.01, p < 0.001, respectively). Furthermore, methylene blue, glibenclamide, Nω-nitro-L-arginine methyl ester, naloxonazine, nor-binaltorphimine, prazosin, yohimbine, and ondansetron pre-treating restored the TPEO anti-nociceptive activity in the FML (phase-II) exemplar (p < 0.05). In phase-II of the FML exemplar, carvacrol (one of the active components of TPEO) also greatly reduced pain (p < 0.001). Likewise, in CVC mice, TPEO altered mechanical allodynia and hyperalgesia. It was attained magnificently that TPEO could exerts antinociceptive effects through the involvement of L-arginine/NO/cGMP/KATP signaling pathway, adrenergic, opioid, and serotonin receptors. Moreover, it is demonstrate that anti-neuropathic activity of TPEO may be mediated by inflammatory function. [Display omitted]